PENGARUH LIKUIDITAS TERHADAP KINERJA KEUANGAN PADA BANK UMUM SYARIAH DI INDONESIA - Widarti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
This study aims to determine the effect of Ratio of Liquid assets to total assets(LTA), Ratio of liquid assets to deposit (LAD), and Ratio Financing to deposit(FDR) on Return On Assets (ROA) at Islamic Commercial Banks registered withJII. 2016-2019 years. The independent variables used in this study are the Ratioof Liquid assets to total assets (LTA), the Ratio of liquid assets to deposits (LAD),and the Ratio of Financing to deposits (FDR). The dependent variable used inthis study is Return On Assets ( ROA). This research is a type of quantitativeresearch. The population of this study is all types of Islamic Commercial BanksRegistered at JII 2016-2019. By using purposive sampling there are as many as13 companies and 52 data used as samples in this study. This data is in the formof annual financial reports that have been audited and published. The analysistechnique used in this research is Multiple Linear Data Regression. Based on theresults of data analysis shows that the Ratio of Liquid assets to total assets (LTA)has a significant effect on Return On Assets (ROA). The ratio of Liquid Assets toDeposit (LAD) and Financing to Deposit (FDR) ratios have no effect on ReturnOn Assets (ROA) in Islamic Commercial Banks.